1997
DOI: 10.1046/j.1365-2168.1997.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance and mood after a weekend on call in a surgical unit

Abstract: A weekend on call has significant deleterious effects on cognitive performance and mood. The findings have implications for staffing levels and the design of duty rosters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 3 publications
0
19
0
3
Order By: Relevance
“…Studies have shown the negative effects of sleep deprivation on clinical performance, mood and cognitive abilities 5 . Surgical procedures have always been a stressful situation for both the patient and patient's relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the negative effects of sleep deprivation on clinical performance, mood and cognitive abilities 5 . Surgical procedures have always been a stressful situation for both the patient and patient's relatives.…”
Section: Discussionmentioning
confidence: 99%
“…The life-time risk of acute appendicitis is around 7% 2 . Although the exact mechanism leading to this condition is still obscure, it is likely that luminal obstruction by external (lymphoid hyperplasia) or internal (inspissated fecal material, appendicoliths) compression plays a key pathogenic role 3,4,5 . The traditional management for acute appendicitis had been an appendectomy as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Taffinder et al 1998 Assistenzärzte nach diesen Dienstwochenenden im Vergleich zu einem Montag morgen nach einem dienstfreien Wochenende fest (vgl. Wesnes et al 1997 Z u einer Ableitung von möglichen Determinanten der Auswirkungen unter schiedlich langer Arbeitstage auf die Leistungsfähigkeit der Arbeitnehmer ist man daher weitgehend auf einen meta-analytischen Vergleich der Studien angewiesen.…”
Section: Alternative Interpretationsmuster Der Mangelnden Verbreitungunclassified
“…Der Unterschied zwi schen den Produktionsfunktionen (2) und (3) ist also lediglich arbeitszeitorgawsatorischer Natur. 56 Wesnes et al 1997;Boudreaux et al 1998;Cydulka et al 1994;Spurgeon/Harrington 1989) Z u einer Ableitung von möglichen Determinanten der Auswirkungen unter schiedlich langer Arbeitstage auf die Leistungsfähigkeit der Arbeitnehmer ist man daher weitgehend auf einen meta-analytischen Vergleich der Studien angewiesen. …”
unclassified
“…8 Cognitivefunction is clearly impaired. 9 With regard to technicalperformance,surgeonsawake all night have been found to make 20% more errors and take 14% longer to completetasksonalaparoscopicsimulator. 10 Sleep deprivation is also dangerous to us personally.…”
mentioning
confidence: 99%